Mapeamento da evolução histórica do uso e ocupação do solo no município de João Pessoa-PB, de 1985 a 2022 - JoãoVictorAraújodaSilva; Luana Ramos de Oliveira; NadjaCecíliadeFreitasSilva; ChristianneMariadaSilvaMoura; SauloRoberto deOliveiraVital (Geopauta)
Mapping land use and occupation is a procedure that makes it possible to analyze how a given area is being occupied and how this reflects on society. With this in mind, this work was developed with the aim of mapping land occupation in the city of João Pessoa-PB, which is one of the fastest growing cities in Brazil. This article was developed by processing images obtained from the INPE system and from Landsat5 and 8. The period from 1985 to 2022 shows changes in use in urban and agricultural areas, with an increase in urban centers. The suppression of vegetation and soil sealing are the most recurrent problems in this process of urban expansion